Enduring CSS : learn to really think about CSS, and how to create CSS that endures continual iteration, multiple authors, and yet always produces predictable results - Frain, Ben (Packt Publishing, 2017)
Learn to really THINK about CSS, and how to create CSS that endures continual iteration, multiple authors, and yet always produces predictable results About This Book Address the problems of CSS at scale, avoiding the shortfalls of scaling CSS. The shortfalls of conventional approaches to scaling CSS. Develop consistent and enforceable selector naming conventions with ECSS. Learn how to organize project structure to more easily isolate and decouple visual components. Who This Book Is For This is a book for working CSS authors involved in large projects. This is a book that tackles create enduring CSS for large-scale projects. What You Will Learn The problems of CSS at scale - specificity, the cascade and styles intrinsically tied to element structure. The shortfalls of conventional approaches to scaling CSS. The ECSS methodology and the problems it solves. How to develop consistent and enforceable selector naming conventions with ECSS. How to organise project structure to more easily isolate and decouple visual components. How to handle state changes in the DOM with ARIA or override selectors. How to apply ECSS to web applications and visual modules. Considerations of CSS tooling and processing: Sass/PostCSS and linting. Addressing the notion of CSS selector speed with hard data and browser representative insight In Detail Learn with me, Ben Frain, about how to really THINK about CSS and how to use CSS for any size project! I'll show you how to write CSS that endures continual iteration, multiple authors, and yet always produces predictable results. Enduring CSS, often referred to as ECSS, offers you a robust and proven approach to authoring and maintaining style sheets at scale. Enduring CSS is not a book about writing CSS, as in the stuff inside the curly braces. This is a book showing you how to think about CSS, and be a smarter developer with that thinking! It's about the organisation and architecture of CSS - the parts outside the braces. I will help you think about the aspects of CSS development that become the most difficult part of writing CSS in larger projects. You'll learn about the problems of authoring CSS at scale - including specificity, the cascade and styles intrinsically tied to document structure. I'll introduce you to the ECSS methodology, and show you how to develop consistent and enforceable selector naming conventions. We'll cover how to apply ECSS to your web applications and visual model, and how you can organize your ...